2004
DOI: 10.1021/es035293l
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Mercury Accumulation Rates Between 5900 and 800 Calibrated Years BP in the High Arctic of Canada Recorded by Peat Hummocks

Abstract: In this paper, we present the first comprehensive long-term record of preanthropogenic rates of atmospheric mercury accumulation in dated peat deposits for the High Arctic of Canada. Geochemical studies of two peat hummocks from Bathurst Island, Nunavut reveal substantial inputs from soil dust (titanium), marine aerosols (bromine), and mineral-water interactions (uranium). Mercury, however, was supplied to these peat mounds exclusively by atmospheric deposition. Mercury concentration measurements and age datin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
(52 reference statements)
5
34
1
Order By: Relevance
“…These values are consistent with pre-anthropogenic atmospheric Hg fluxes in the Arctic and temperate zone, which were also 10e20 times lower than recent deposition rates Givelet et al, 2004).…”
Section: The Distribution Of Trace Elementssupporting
confidence: 85%
“…These values are consistent with pre-anthropogenic atmospheric Hg fluxes in the Arctic and temperate zone, which were also 10e20 times lower than recent deposition rates Givelet et al, 2004).…”
Section: The Distribution Of Trace Elementssupporting
confidence: 85%
“…The 16 toppermafrost samples as well as permafrost cores represent contrasting soil types within the area downstream from the ice-dammed lake where the flooding and the associated erosion is considered most important for sediment transport in the Zackenberg River. Few studies have previously measured Hg concentrations in permafrost (Givelet et al, 2004;Outridge and Sanei, 2010). Those studies reported Hg concentrations in permafrost of peat sites ranging from~0.010 to 0.050 mg kg −1 , which is within the Hg concentration range measured in this study.…”
Section: Hg Concentrations In Soil Permafrost and Snow Within The Zasupporting
confidence: 79%
“…Several historic sediment and peat bog records from remote sites in both the northern and the southern hemispheres indicate a 2-4 fold increase in Hg deposition since pre-industrial times (Engstrom and Swain, 1997;Bindler et al, 2001;Lamborg et al, 2002;Shotyk et al, 2003;Givelet et al, 2004;Fitzgerald et al, 2005;Shotyk et al, 2005). North American and European Hg emissions are decreasing while those in Asia and Africa are increasing but the latter changes are less well documented and thus carry a larger uncertainty (see Table 1).…”
Section: Worldwide Anthropogenic Mercury Sourcesmentioning
confidence: 99%